2018
DOI: 10.1002/smll.201804326
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Microfluidic Mixers—A Comparative Study on Mixing Unit Performances

Abstract: One of the basic operations in microfluidic systems for biological and chemical applications is the rapid mixing of different fluids. However, flow profiles in microfluidic systems are laminar, which means molecular diffusion is the only mixing effect. Therefore, mixing structures are crucial to enable more efficient mixing in shorter times. Since traditional microfabrication methods remain laborious and expensive, 3D printing has emerged as a potential alternative for the fabrication of microfluidic devices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 34 publications
(53 reference statements)
3
85
0
3
Order By: Relevance
“…A comparison of four different 3D printed micromixers is given by. Enders et al 33 which includes a comprehensive numerical and experimental analysis of the mixing performance. This study showed that chaotic mixing, induced by the geometry of the micromixers, signicantly increases the mixing performance.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of four different 3D printed micromixers is given by. Enders et al 33 which includes a comprehensive numerical and experimental analysis of the mixing performance. This study showed that chaotic mixing, induced by the geometry of the micromixers, signicantly increases the mixing performance.…”
Section: Introductionmentioning
confidence: 99%
“…In case of Tesla channel, fluid streams are divided and recombined by convection, bringing molecules which were initially far separated to near vicinity [20,26]. The Peclet number Pe=VWD, taking the flow rate 22.5 mL/min, Pe=68000, meaning that transversal convection in Tesla structure dominates the mixing procedure.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, we chose microfluidic chip with Tesla structure to optimize PEI‐antigen nanoparticles preparation. The Tesla structure is effective in enhancing the mixing of fluids by creating transversal convection [20,21]. We compared the formation of antigen‐containing polyplexes in Tesla microfluidics with BM and non‐Tesla microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…The rise of experiment-specific, customized 3D-printed labware can remove this artificial and regrettable limitation. Moreover, high-resolution 3D printing technology can open the door to manufacturing even complex devices at a micro scale [ 48 ]. Personalized experimental equipment or whole cultivation systems of almost limitless complexity can potentially be produced from start to finish within just a few hours—offering for a tremendous potential for pursuing experimental parallelization within a highly controllable environment.…”
Section: Discussionmentioning
confidence: 99%